Barrow, gilt comparisons -- gains and carcass composition at various ration protein levels - Donald H Kropf; L H Kasten; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1968)
Many studies have reported that barrows gain more rapidly than gilts, but gilts excell in carcass muscling and trimness. Recently, considerable interest has been directed toward determining ration protein needs of barrows compared to gilts, with a strong possibility that these protein needs differ. If this is true, feeding barrows and gilts separately may be recommended.; Swine Day, Manhattan, KS, September 26, 1968
Keywords: Swine day; 1968; Swine; Barrow; Gilt; Gains